PERKEMBANGAN INDIKATOR MAKRO EKONOMI KOTA BANDUNG KUARTA II-2019 - Santoso, Teguh; Kharisma, Bayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2019)
Analysis of the development of macroeconomic indicators is commonly done as an evaluation material and economic management strategy in the future. There are 3 macroeconomic indicators that are commonly used at the regional level, namely the rate of inflation, economic growth and employment. This study aims to conduct an analysis of the three indicators at the Bandung City level. The research method used is descriptive and quantitative analysis. Descriptive analysis is based on the movement of data presented through graphs and tables. While quantitative analysis is more focused on calculating the inflation variable projections and correlation analysis between macroeconomic variables. Based on the results of descriptive analysis, it is known that the Bandung City inflation indicator was relatively maintained in the second quarter of 2019. Even though there is a moment of Eid, the inflation rate is still under control, and even tends to decrease in June 2019. However, the inflation rate is predicted to increase in the third quarter of 2019. Food commodity inflation is predicted to occur due to the peak of the dry season in August-September. On the indicator of the rate of economic growth, the most recent data for 2017 shows a decline in the growth rate, by 7.21%. The achievement of economic growth is also the lowest since 2011. On the employment indicator, there is an irrelevant relationship between the Economic Growth Rate (LPE) Labor Force Participation Rate (TPAK), and the Open Growth Rate